UJI DAYA HAMBAT EKSTRAK KELOPAK BUNGA ROSELLA (HIBISCUS SABDARIFFA L.) SEBAGAI ANTIBAKTERI STAPHYLOCOCCUS AUREUS - Tedy Febriyanto; Resva Meinisasti; Jon Farizal; Diajeng Dea Resya Mawardi (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2019)
ABSTRACT Background: Infection is one of the biggest health problems in the world. According to WHO 2015 based on YLL (Years Of Life Lost) data in developing countries infectious diseases are still the main cause of death. Staphylococcus is the main cause of purulent infections in humans found in the nasal cavity and skin of most human populations. One skin disease caused by the bacterium Staphylococcus aureus is a boil. Staphylococcus aureus has experienced antibiotic resistance. So from that the alternative that can be done is by using natural or traditional ingredients, namely by utilizing rosella flower petals (Hibiscus Sabdariffa L.). The purpose of this study was to determine the inhibitory power of rosella (Hibiscus Sabdariffa L.) flower extract on the growth of Staphylococcus aureus bacteria. Method: This study is a descriptive study with four treatments with 70%, 75%, 80% and 85% concentration variations using Univariate statistical test data analysis. Results: Diameter of inhibition zone formed at 70% concentration of 14.4 mm, concentration of 75% 15.7 mm, 80% concentration of 16.4 mm, 85% concentration of 19.6 mm. Conclusion: Ethanol extract of rosella flower petals (Hibiscus Sabdariffa L.) has antimicrobial substances which can inhibit the growth of staphylococcus aureus bacteria at a concentration of 85% with a mean inhibitory zone 19.6 mm and categorized as strong.